Maternal smoking during pregnancy and infant stress response: Test of a prenatal programming hypothesis - Stroud, Laura R. (2014)
BACKGROUND: Maternal smoking during pregnancy (MSDP) is associated with early and long-term neurobehavioral deficits; however mechanisms remain unknown. We tested the hypothesis that MSDP programs the hypothalamic pituitary adrenocortical (HPA) axis of the offspring leading to adverse outcomes. In an intensive, prospective study, we investigated associations between MSDP and infant cortisol stress response and explored whether alterations in cortisol response were mediated by epigenetic modulation of the placental glucocorticoid receptor gene (NR3C1). METHODS: Participants were 100 healthy mother-infant pairs (53% MSDP-exposed; 42% female) from a low income, racially/ethnically diverse sample (55% minorities). MSDP was assessed by timeline followback interview verified by saliva and meconium cotinine. Infant cortisol responses to a neurobehavioral exam were assessed 7 times over the first postnatal month. Methylation of placental NR3C1 promoter exon 1F was assessed using bisulfite pyrosequencing in a subsample (n=45). RESULTS: MSDP-exposed infants showed significantly and persistently attenuated basal and reactive cortisol levels over the first postnatal month vs. unexposed infants. Exploratory analyses revealed that MSDP was associated with altered methylation of the placental NR3C1 promoter; degree of methylation of the placental NR3C1 was associated with infant basal and reactive cortisol over the first postnatal month and mediated effects of MSDP on infant basal cortisol. CONCLUSIONS: Results provide initial support for our hypothesis that MSDP programs offspring HPA (dys) regulation. Epigenetic regulation of placental GR may serve as a novel underlying mechanism. Results may have implications for delineating pathways to adverse outcomes from MSDP.